Evidence of misery perfusion and risk for recurrent stroke in major cerebral arterial occlusive diseases from PET. Issue 1 (July 1996) - Yamauchi, H; Fukuyama, H; Nagahama, Y; Nabatame, H; Nakamura, K; Yamamoto, Y; Yonekura, Y; Konishi, J; Kimura, J
Abstract : OBJECTIVES–In major cerebral arterial occlusive diseases, patients with inadequate blood supply relative to metabolic demand (misery perfusion) may be at increased risk for cerebral ischaemia. This study investigated whether patients showing misery perfusion on PET have a high risk of recurrent ischaemic stroke. METHODS–The relation between the regional haemodynamic status of cerebral circulation and the subsequent risk of recurrent stroke was prospectively evaluated in 40 patients with symptomatic internal carotid or middle cerebral arterial occlusive diseases who underwent PET. Patients were divided into two haemodynamic categories according to the mean hemispheric value of oxygen extraction fraction in the hemisphere supplied by the artery with symptomatic disease: patients with normal oxygen extraction fraction and those with increased oxygen extraction fraction (misery perfusion). All patients were followed up for at least 12 months. RESULTS–The one year incidence of ipsilateral ischaemic strokes for patients with normal oxygen extraction fraction and those with increased oxygen extraction fraction were two of 33 and four of seven patients respectively. A significantly higher incidence of ipsilateral strokes was found in patients with increased oxygen extraction fraction (Fisher's exact test; P = 0.005). In patients with increased oxygen extraction fraction, three of four strokes were watershed infarctions and the location of the infarction corresponded with the area of increased oxygen extraction fraction. CONCLUSION–These findings contradict conclusions of a previous study and suggest that patients with major cerebral arterial occlusive diseases and misery perfusion have a high risk for recurrent ischaemic stroke.